Prepulse inhibition in patients with fragile X-associated tremor ataxia syndrome - Schneider, Andrea; Ballinger, Elizabeth; Chavez, Alyssa; Tassone, Flora; Hagerman, Randi J.; Hessl, David (Neurobiology of aging, 2012)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is a late onset neurodegenerative disorder that affects carriers of the fragile X premutation, typically after age 50. Common symptoms include intention tremor, ataxia, neuropathy, autonomic dysfunction, cognitive decline, and dementia. The objectives of this study were to determine if patients with FXTAS have altered prepulse inhibition (PPI; a measure of sensorimotor gating), and to study possible correlations between PPI, molecular status, and cognitive performance. A passive acoustic PPI paradigm was applied in 163 subjects; 121 carriers of the fragile X premutation, and 42 healthy controls. There were significant differences in PPI between premutation carriers with FXTAS and controls at PPI 60 ms, and at 120 ms. This effect was more prominent in the male FXTAS patients. There was a tendency to an impaired PPI in female premutation carriers at the 120 ms condition. There was a significant correlation between the PPI deficit and a higher CGG repeat number. The results show an impairment in sensorimotor gating processes in male carriers of the fragile X premutation, which is more prominent in patients with FXTAS.